Analysis of the Standards and Characteristics of The Failed State - Tahseen Wsu Abdullah; Ahmed Babakr Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
The state has been busy with it as a major subject of political science and has done its work in various ways, in a way that some political science has been state-controlled, and the country has been A real need for organizing and manageing the community, human it's documents, and providing security are a necessity for creating a political one to style Their lives were transferred from one stage to another, and the state form was different from the world to another. One of the most important issues of this process has been the failure of countries to carry out their duties, or the failure of countries that many countries, especially in Asia, Africa and the Middle East, cannot perform their duties. This situation, together with the various problems facing the countries, will cause regional and global problems as well as the national problems that will lead to civil war. Although there is no unilateral reason for the failure of states, the reason for the failure of states can be attributed to many historical, cultural, social, economic and global factors and its reflection shall be different from that of any country.